A clinical analysis of uterine artery embolisation in the treatment of placenta praevia or placenta praevia state. (October 2014) - Ji, W.; Wang, W.; Sun, S.; Wu, J.; Xu, W.; Tao, D.; Xu, C.; Fu, X.; Chen, Y.; Yang, S.
Abstract The aim of this study was to investigate the efficiency of uterine artery embolisation (UAE) for postpartum haemorrhage (PPH) related to placenta praevia. A total of 45 women with placenta praevia or placenta praevia state underwent UAE before inducing labour. The locations of uterine artery and placenta were determined through selective and super-selective catheterisation into the internal iliac artery and uterine artery digital subtraction angiography (DSA). The target arteries were then super-selectively catheterised and embolised using small pieces of gelatin sponge. The above processes were repeated until the darkly stained areas of placenta were no longer developing. The success rate of UAE was 100%. There was no longer haemorrhage after embolisation for all the cases of labour induction and the average volume of blood loss was 56 ml. UAE is an effective, reliable and minimally traumatic treatment method for preventing postpartum haemorrhage after induction of labour in patients with placenta praevia state.